2022
DOI: 10.3390/mi14010057
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Research Progress in Selective Laser Melting (SLM)

Abstract: SLM (Selective Laser Melting) is a unique additive manufacturing technology which plays an irreplaceable role in the modern industrial revolution. 3D printers can directly process metal powder quickly to obtain the necessary parts faster. Shortly, it will be possible to manufacture products at unparalleled speeds. Advanced manufacturing technology is used to produce durable and efficient parts with different metals that have good metal structure performance and excellent metal thermal performance, to lead the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 83 publications
0
30
0
Order By: Relevance
“…The results of the study [23] showed that the ability of cells to vascularize and the proportion of bone area on scaffolds with pores of irregular size were stronger and larger, respectively, than on regular ones, while the mechanical properties of irregular scaffolds were better than those of regular ones. Gao B. et al (2023) in a review article [24] note the advantage of SLM over other 3D printing technologies, such as the aforementioned EBM, DED (Directed Energy Deposition), or DMLS (Direct Metal Laser Sintering), as the ability to produce a product with high mechanical load capacity, no worse than traditional processes, and even better than forging. However, high porosity reduces the mechanical strength of the implant, which is a challenge.…”
Section: Additive Manufacturing Of Orthopedic Implants: Advantages An...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study [23] showed that the ability of cells to vascularize and the proportion of bone area on scaffolds with pores of irregular size were stronger and larger, respectively, than on regular ones, while the mechanical properties of irregular scaffolds were better than those of regular ones. Gao B. et al (2023) in a review article [24] note the advantage of SLM over other 3D printing technologies, such as the aforementioned EBM, DED (Directed Energy Deposition), or DMLS (Direct Metal Laser Sintering), as the ability to produce a product with high mechanical load capacity, no worse than traditional processes, and even better than forging. However, high porosity reduces the mechanical strength of the implant, which is a challenge.…”
Section: Additive Manufacturing Of Orthopedic Implants: Advantages An...mentioning
confidence: 99%
“…It should also be noted that in a review article [24], poor surface roughness is noted as a disadvantage of SLM technology; however, there are currently no systematic studies on how SLM or SLS (Selective Laser Sintering) parameters affect the surface roughness of scaffolds or the relationship between roughness and biocompatibility of scaffolds [26]. Thus, it can be assumed that the high roughness values achieved in the SLM process (for example, the average roughness Ra = 26.6 ± 3.4 µm of 3D printed tensile specimens of the titanium alloy Ti6Al4V mentioned in [19]) may increase the biocompatibility of 3D printed titanium implants.…”
Section: Additive Manufacturing Of Orthopedic Implants: Advantages An...mentioning
confidence: 99%
“…It is often common to see rougher surface finishes after printing, which requires post‐processing (i.e., polishing, etching, coating), typically due to the particle size, distribution, shape regularity, diffusion of particles with the neighboring ones, and fluidity affecting the smoothness and thickness of the layer. [ 158 ] Generally, these 3D printing methods for batteries mostly produce a dot or line size above 10 µm and may lose the resolution below a single‐digit micron size.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…Different types of materials like plastics [55,56], concrete [57,58], composites [59,60], elastomers [61,62], polymers [63][64][65], metals and alloys [66][67][68][69][70][71][72], and non-metals [73,74] can be used for developing components. Commonly used 3D printing processes for stainless steel alloys, aluminum alloys, titanium alloys, and super alloys are laser powder bed fusion (LPBF) [75][76][77][78][79][80][81][82][83] wire arc direct energy deposition [84][85][86], laser metal deposition [87,88], and additive friction stir deposition [89][90][91] processes. The current research in additive manufacturing on aluminum alloys [92][93][94][95][96][97][98][99][100][10...…”
Section: Introductionmentioning
confidence: 99%